PENGARUH KUALITAS PELAYANAN PRIMA (SERVICE EXCELLENCE), PORSI BAGI HASIL DAN TINGKAT PENDAPATAN NASABAH TERHADAP TABUNGAN FIRDAUS PADA PT. BANK ACEH SYARIAH LANGSA - Antoni, Muhammad Safri (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2018)
This study aimed to test the Influence of Excellent Service Quality, Portion of Profit Sharing and Savings Income Level of Customers of Firdaus Savings at PT. Bank Aceh Syariah Langsa empirically. The method used for data analysis was OLS (Ordinary Least Square) with double linear regression estimation model based on the results of data processing by using Eviews software program. From the research result, R2 value of 0.851 was obtained. This means that approximately 85.1 percent of the proportion of independent variables used could explain the dependent variable variation in that model. Whereas the remaining of 14.9 percent was explained by other variables that were not used in this study. While the estimation results showed that the F-count was greater than the F-table (F-calculated = 22.71 > F-table = 2.67) for the function of the amount of the savings equation. It means that all independent variables used in the estimation of this analysis model namely service, profit sharing, and income jointly gave significant effect on the amount of Firdaus Savings at PT. Bank Aceh Syariah Langsa. Thus the Coefficient of service showed a value of 1.028 which means that the higher the level of service which was equal to 1.028 percent, the savings would increase the amount of Firdaus Savings at PT. Bank Aceh Syariah Langsa for about 1.028 percent and was elastic, the Coefficient of profit sharing showed a value of 1.425 which means that any increase of profit sharing in the yield of 1.425 percent, the savings would increase the amount of Firdaus Savings at PT. Bank Aceh Syariah Langsa for about 1.425 percent and was elastic. The Coefficient of income showed a value of 0.737 which means that any increase in revenues of 0.737 percent, the savings would increase the amount of Firdaus Savings at PT. Bank Aceh Syariah Langsa for about 0.737 percent and was inelastic. Service is one of the dominant factors that affect the amount of savings in Islamic banks, then it must be put into consideration by any Islamic banks to keep improving their services.